Control of crystallization behaviour of supercooled liquid composed of lithium disilicate on platinum substrate - Masanori Tashiro (Nature Portfolio, 2017)
Abstract Crystalline lithium disilicate (Li2Si2O5, LS2) materials, which have excellent mechanical properties with high transparency, should be obtained efficiently through the crystallization of supercooled liquid composed of LS2. However, in addition to LS2, a lithium monosilicate (Li2SiO3, LS) phase is also precipitated during the crystallization of the liquid. The precipitation of the LS phase renders it difficult to obtain a single-phase LS2 material. Here, we show that by altering the oxygen partial pressure, it is possible to change the selectivity of the precipitated phase by controlling the interfacial phenomena that occur between the liquid and platinum contact material. During cooling of the supercooled liquid, the type of precipitated phase can be controlled by optimizing the atmosphere and type of contact material. This methodology can be applied for the fabrication of other functional materials and does not require the use of other additives.